أثر السياسات النقدية في معدلات التضخم في بلدان نامية مختارة للمدة 1980 - 2003 - الدليمي، فواز جار الله نايف; السبعاوي، عبدالله خضر عبطان (جامعة الموصل - كلية الإدارة والاقتصاد, 2009)
تعد السياسة النقدية أحد أهم السياسات الاقتصادية المتبعة في تنظيم الحياة الاقتصادية وحل مشاكلها، وتستند السياسة النقدية التي تتبعها السلطات في وقت ما على النظرية أو الأفكار النقدية السائدة في ذلك الوقت وتعد انعكاساً لها، وبالتالي تحدد تلك النظرية أو الأفكار الهدف من السياسة النقدية، وكذلك الكيفية المستخدمة لبلوغ أو تحقيق ذلك الهدف، ومن الناحية العملية كانت سياسية البنك المركزي تنفذ عن طريق إجراء التغيرات في احتياطيات المصارف التجارية والقيام بعمليات السوق المفتوحة وأسعار الخصم التي ما تزال أساس السياسية النقدية حتى في معناها الواسع. \ وينطلق البحث من فرضية مفادها "ثمة علاقة بين مشكلات التضخم وبين توسع المعروض النقدي في البلدان النامية، فيعتمد البحث فرضية مفادها أن للتضخم آثاراً اقتصادية غير مرغوب فيها في الأداء الاقتصادي لبلدان العينة موضوع الدراسة". وتم توفيق معادلات الانحدار لدول العينة (13 دولة) باستخدام طريقة المربعات الصغرى (OLS) من خلال الحزمة البرمجية (Minitab). \ وبعد تحليل البيانات كانت العلاقة موجبة بين معدل التضخم وعرض النقود وذات تأثير معنوي بما يتفق مع النظرية الاقتصادية في حين تباينت نتائج التحليل بالنسبة لأسعار الفائدة وسعر الصرف. The monetary policy is considered to be one of the most important economic policies used in organizing economic life and solving its problems. The monetary policy followed by authorities at one time is based on a theory or monetary ideas prevailed at that time which in turn formulates the aim of the monetary policy and the method to achieve that aim. Practically speaking, the policy of the Central Bank was implemented by changing the reserves of the commercial banks and practicing the operations of the open market and discount prices which still constitute the basis of the monetary policy even in its wide concept. The research stems from the premise that "there is a relationship between the problems of inflation and the expansion of the monetary supply in developing countries. The research premises that economic effects of inflation unwanted in the economic performance of countries in the sample in question." The regression equations for the sample (13 States) have been done using the method of least squares (OLS) through a software package (Minitab). \ Having analyzed data, the relation was positive between inflation rate and money supply with abstract effect in accordance with economic theory. The analysis result varied concerning the rate prices and exchange price.
Keywords: السيولة النقدية -- السياسة النقدية -- التضخم المالي -- الدول النامية -- التدفقات النقدية -- أسعار الفائدة